The Increase in Longitudinally Measured Sleepiness Across Adolescence is Related to the Maturational Decline In Low-Frequency EEG Power - Campbell, Ian G. (Associated Professional Sleep Societies, LLC, 2007)
OBJECTIVES: A changing sleep schedule that reduces sleep duration is thought to produce the increasing daytime sleepiness of adolescents. We tested the hypothesis that adolescent daytime sleepiness also results from adolescent brain maturational processes indexed by declining delta electroencephalographic (EEG) activity. DESIGN: Data are from the first 3 years of a semilongitudinal study of EEG changes in adolescence. All-night EEG was recorded semiannually. SETTING: EEG was recorded with ambulatory recorders in the subjects' homes. PARTICIPANTS: Thirty-one subjects were 9 years old (cohort C9), and 38 subjects were 12 years old (cohort C12) at the start of the study. MEASUREMENTS: EEG power density (power/minute) was calculated for the first 5 hours of non-rapid eye movement sleep. Subjects rated sleepiness on a modified Epworth Sleepiness Scale. Habitual sleep schedules were assessed with self-reports and actigraphy. RESULTS: In C9 subjects, sleepiness increased slightly and was related only to age. In C12 subjects, the increase in subjective sleepiness was related to changes in age, bedtime, time in bed, and a wide frequency range of EEG power density. Sleepiness was not related to rise time, non-rapid eye movement sleep duration, rapid eye movement sleep duration, or total sleep time. With sleep schedule measures statistically controlled, the increase in sleepiness in the C12 group was strongly related to declining delta power density and, unexpectedly, even more strongly related to declining theta power density. CONCLUSIONS: The data support our hypothesis that, independent of sleep schedule changes, increasing adolescent daytime sleepiness is related to brain maturational changes indexed by declining EEG power. Our working hypothesis is that the declines in delta and theta power are correlates of an adolescent synaptic pruning that reduces waking arousal levels. CITATION: Campbell IG; Higgins LM; Trinidad JM; Richardson P; Feinberg I. The increase in longitudinally measured sleepiness across adolescence is related to the maturational decline in low-frequency EEG power. SLEEP 2007;30(12):1677-1687.